Novel Psychological Formulation and Treatment of “Tic Attacks” in Tourette Syndrome - Robinson, Sally; Hedderly, Tammy (Frontiers in Pediatrics, 2016)
One important, but underreported, phenomena in Tourette Syndrome (TS) is the occurrence of ‘tic attacks’. These episodes have been described at conferences as sudden bouts of tics and/or functional tic-like movements, lasting from 15 minutes to several hours. They have also been described by patients in on-line TS communities. To date, there are no reports of tic attacks in the literature. The aim of this article is to stimulate discussion and inform clinical practices by describing the clinical presentation of 12 children (mean age 11 years 3 months; sd=2 years 4 months) with TS and tic attacks, with a detailed case report for one case (JT, 13 years). These children commonly present acutely to casualty departments and undergo unnecessary medical investigations. Interestingly, all children reported co-morbid anxiety, with worries about the tics themselves and an increased internal focus of attention on tics once the attacks had started. In keeping with other children, JT reported a strong internal focus of attention, with a relationship between physiological sensations/tic urges, worries about having tic attacks and behavioural responses (e.g. body scanning, situational avoidance, other responses). In our experience the attacks reduce with psychological therapy, for example, JT attended 13 sessions of therapy that included metacognitive and attention training techniques, as well as cognitive behavioural strategies. Following treatment an improvement was seen across a range of measures assessing tics, mood, anxiety and quality of life. Thus, psychological techniques used to treat anxiety disorders are effective at supporting a reduction in tic attacks through modifying attention, worry processes and negative beliefs. It is hypothesised that an attentional style of threat monitoring, difficulties tolerating internal sensory urges, cognitive misattributions and maladaptive coping strategies contribute to the onset and maintenance of tic attacks. These cases provide support for the view that tic attacks are triggered and maintained by psychological factors, thereby challenging the view that tic attacks merely reflect extended bouts of tics. As such, we propose that the movements seen in tic attacks may resemble a combination of tics and functional neurological movements, with tic attacks reflecting episodes of panic and anxiety for individuals with TS.